THE INFLUENCE OF POND AND GENERAL GRADUATES ON THE LEVEL OF QUR'AN MEMORATION AND ACADEMIC ACHIEVEMENT OF HAFIDZPRENEUR STUDENTS - Nurmala, Nurmala; Purba, Asnan (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
The study aimed to assess the impact of graduates from Islamic boarding schools and general schools on Quran memorization levels and academic grades of Hafidzpreneur students. The method used was a dummy variable regression with data processing using Microsoft Excel 2016. The primary data used were collected through questionnaires distributed to Hafidzpreneur students via Google Forms. The data were analyzed using regression analysis, partial F-test, and simultaneous F-test. The R-squared value in this study was 0.416, indicating that the dependent variable (Quran memorization) can be explained by the independent variables (graduates from Islamic boarding schools and general schools, and academic performance) to the extent of 41.6%. The remaining 58.4% can be explained by other variables. The study found that graduates from both Islamic boarding schools and general schools negatively affected Quran memorization, as indicated by a probability of 0.34 > α = 0.05. Additionally, academic performance negatively influenced Quran memorization, with a probability of 7.52 > α = 0.05. The study concluded that students from both Islamic boarding schools and general schools, as well as academic performance, do not significantly affect the level of Quran memorization among Hafidzpreneur students. The study has significant implications in increasing understanding about the relationship between graduates from general and Islamic boarding schools on Quran memorization and academic levels. The study's results can help educational institutions develop new programs that combined religious and general education, particularly for students interested in becoming Hafidzpreneur.